Review of Methods for Prediction and Identification of Small Faults - Yan, Zhaopeng (International Journal of Natural Resources and Environmental Studies, 2024)
Fault system is the oil and gas reservoir is one of the main control factors of characteristic changes especially, for dense reservoirs, so it is very important for quality reservoir prediction. However, due to the complex relationship and contradiction between the genesis and scale problems of small faults and the characteristics and resolution of seismic response, the seismic detection technology of small fault development zones is one of the current research hotspots. Seismic attribute analysis is one of the effective means for small fault identification and prediction. Various types of seismic attributes can be obtained by doing different mathematical and physical transformations on seismic data, and various different kinds of seismic attributes can be obtained based on seismic data. Different seismic attributes can describe different geological features, and a single seismic attribute has good ability to identify faults, but a single seismic attribute to predict reservoir The single seismic attribute has good ability to identify faults, but the single seismic attribute may have multiple solutions when predicting reservoir parameters. Therefore, by preferring multiple attributes that can reflect the reservoir characteristics in the work area for analysis, multiple solutions can be reduced and the prediction accuracy can be improved, which is very practical in fault prediction.